'I thought this was a Christian thing?' Exploring virtuous and exclusionary cycles in faith-based social action. (10th February 2014) - Pathak, Pathik; McGhee, Derek
Abstract : The role of faith groups as welfare providers has received notable attention in the past few years as religious groups have become increasingly active in the voluntary sector. Developing Baker's ideas on 'local performative theologies', we examine data from semi-structured interviews focusing on Christian interdenominational networks and forms of collaboration which underpin faith-based projects in a city in the South of England. Our particular focus is on the development of a qualitative understanding of city-wide interdenominational networks and their role in sustaining faith-based projects. We find that while there is a discernible shift towards faith through praxis, there has been insufficient attention to virtuous and exclusionary circuits of networks and collaboration which consolidate boundaries of inclusion and exclusion between faith groups.